2015
DOI: 10.1155/2015/507848
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Activity Prevents the Unloading Induced Loss of Bone Mass, Architecture, and Strength in Rats

Abstract: We investigated whether swimming activity associated with a three-week period of hypoactivity could prevent the deleterious effects of disuse on the tibias of tail-suspended rats. Forty Wistar rats were divided into five groups: (HS) permanently hindlimb suspension rats; (HS + Swim) rats submitted to unloading interrupted by swimming exercise; (HS + WB) hindlimb suspension rats with interruption for regular weight bearing for the same length of time as the HS+Swim rats; (Control) control rats that were allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
9
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
5
9
1
1
Order By: Relevance
“…This group found that swimming during suspension resulted in significant increases in BMD (+43%; p < 0.001) compared with the 20% increase that we report. They also report increases in Tb.Th (+58%), BV/TV (+85%), and Tb.N (+27%), compared with +20% Tb.Th, +32% BV/TV, and +10% Tb.N that we report with our experiment . Falcai and colleagues also reported a lesser effect of suspension and swimming on cortical bone, similar to our findings .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This group found that swimming during suspension resulted in significant increases in BMD (+43%; p < 0.001) compared with the 20% increase that we report. They also report increases in Tb.Th (+58%), BV/TV (+85%), and Tb.N (+27%), compared with +20% Tb.Th, +32% BV/TV, and +10% Tb.N that we report with our experiment . Falcai and colleagues also reported a lesser effect of suspension and swimming on cortical bone, similar to our findings .…”
Section: Discussionsupporting
confidence: 93%
“…They also report increases in Tb.Th (+58%), BV/TV (+85%), and Tb.N (+27%), compared with +20% Tb.Th, +32% BV/TV, and +10% Tb.N that we report with our experiment . Falcai and colleagues also reported a lesser effect of suspension and swimming on cortical bone, similar to our findings . Swift and colleagues found similar results to the above: Trabecular bone is more affected than cortical bone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The closed and minimal exposition of this fracture model with stabilization is an adequate experimental method because it allows healing by callus formation (secondary healing) without interference of fracture misalignment that might make it difficult to interpret the results 28,29 . The parameters of bone and callus quality that we used are currently employed in experimental practice [30][31][32] . We chose the post-fracture periods of 14 and 28 days because these time intervals represent important landmarks for the femoral fracture Nandrolone decanoate appears to increase bone callus formation in young adult rats after a complete femoral fracture Guimarães APFGM et al…”
mentioning
confidence: 99%